2008
DOI: 10.4103/1817-1737.39635
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Arabic version of the asthma control test

Abstract: PURPOSE:Asthma control test (ACT) has been devised to assess the degree of asthma control in out-patients setting. The aim of this study is to validate the Arabic version of ACT.MATERIALS AND METHODS:Patients completed the Arabic version of ACT during regular visit to one of two asthma specialists. Spirometry was obtained. The asthma specialist rated asthma control using a 5-point scale and indicated modification in management as step up, same or step down of asthma treatment.RESULTS:40 patients completed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 9 publications
1
74
1
Order By: Relevance
“…The area under the ROC curve (AUC) was acceptable at 0.85 (95% CI 0.80 to 0.88) and of similar magnitude to previous findings for the ACT. 7,14,[17][18][19][20] The ACT has been shown to be a reliable tool by previous authors, 7,8,[14][15][16][17]21,22 and this is confirmed by this study in a Vietnamese outpatient setting in which Cronbach's alpha reached 0.83, indicating a high consistency among the answers to the five questions.…”
Section: -9supporting
confidence: 74%
“…The area under the ROC curve (AUC) was acceptable at 0.85 (95% CI 0.80 to 0.88) and of similar magnitude to previous findings for the ACT. 7,14,[17][18][19][20] The ACT has been shown to be a reliable tool by previous authors, 7,8,[14][15][16][17]21,22 and this is confirmed by this study in a Vietnamese outpatient setting in which Cronbach's alpha reached 0.83, indicating a high consistency among the answers to the five questions.…”
Section: -9supporting
confidence: 74%
“…[18][19][20] For children, the cACT has more validation data than other tools that target children with asthma. [37][38][39] Also, the populations used in the validation studies vary between tools.…”
Section: Discussionmentioning
confidence: 99%
“…9,15,16 The substantially low correlations between the ACT scores and physiologic measures of asthma, such as FEV 1 values and F ENO , support the notion that asthma control cannot be inferred from physiologic measures alone. 14,17 Furthermore, the ACT has been validated in many languages [18][19][20][21][22][23] and in different settings, including in asthma specialist consultations, 9 in primary care, 13 in pharmacies, 24 by mail, 25 by speech-recognition telephone calls, 26 and over the internet. 27 …”
Section: Validitymentioning
confidence: 99%
“…The SINA expert panel recommends the utilization of ACT to assess control as it is validated, practical, and simple to use (Evidence D) [Box 10]. [113114] A score of ≥20 indicates controlled asthma, 16–19 partially controlled asthma, and <16 indicates uncontrolled asthma. [5253] The clinically important change in ACT score is considered to be ≥3 units change.…”
Section: Approach To Asthma Managementmentioning
confidence: 99%